Medan kunden rakas växer skägget - Lundbladh, Carl-Erik (Nordiske Studier i Leksikografi, 2003)
In a comprehensive dictionary which is published as it is being made over an extended period of time there is a great risk of inconsistences and fallacies in cross-references. If the object of desription is modern language, there is also a risk that the earlier parts of the dictionary will be more or less outdated when the last parts are made. This paper intends to show how the Swedish Academy Dictionary deals with problems caused by a sometimes outdated, incomplete or erroneous description in earlier parts of the dictionary.